Genetic Animal Models of Idiopathic Generalized Epilepsies: What Can We Learn from Them? - Bernard Lakaye; Laurent Nguyen (Biomedicines, 2025)
The use of animal models of idiopathic generalized epilepsy (IGE) is of great importance in the field of epilepsy research, with IGE affecting more than 20 million people worldwide. IGEs are characterized by a high degree of genetic heterogeneity, which makes it difficult to understand the underlying mechanisms leading to seizures. The development of animal models, whether spontaneous or resulting from genetic manipulation, has significantly contributed to our understanding of the pathological processes underlying certain IGEs, notably absence epilepsy. Research suggests that the concept of generalized epilepsy covering the whole brain should be replaced by a model in which the thalamus and its various nuclei are integrated into thalamo-cortical loops. These then assume distinct roles in the generation and generalization of seizures, which may differ across the spectrum of IGE disorders. The study of epileptogenesis is also essential: this area of research, grounded in systematic developmental neuroscience, examines the intermediate stages of neuronal activity to determine when, and how, functional development diverges between healthy and pathological states. Understanding nervous system development requires a comprehensive view of how anatomic, molecular, and genetics factors relate to neuronal activity. The emerging use of optogenetic methods and human assembloids will greatly aid our understanding of the mechanisms underlying these processes.